Kritik dan Komentar Pendidikan Esensialis - Sulhatul Habibah (Al-Riwayah : Jurnal Kependidikan, 2019)
Humans are cultural beings. Culture here is understood as a result of the creation of human reason. Essentialist schools in education offer concepts that have strong roots in cultural values in the past. Essentialist education sees education as having a fixed foundation and not changing from time to time. The question is how far is the relevance of essentialist education in schools are able to be maintained in front of changing reality and challenges? This article attempts to analyze essentialist educational discourse at the level of its application in school. Critics and comments on this paper aims to find out the basic arguments for their strengths and weaknesses.